Digital marketing strategy for hospitals in the post Covid-19 pandemic in 2023: A literature review - Astriana Astriana; Wahyu Sulistiadi (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2024)
Background: The healthcare industry is currently facing significant pressure due to the emergence of Covid-19. The Covid-19 pandemic has had adverse effects on the global economy, industries, and organizations, impacting marketing strategies and expenditures. Due to total lockdown in various regions, digital marketing has become crucial as traditional marketing strategies are no longer effective. One way to gain a competitive edge is to develop an effective marketing strategy. The goal is to inform the public about hospitals, provide information about the facilities and services offered, and build a positive image through the trust of the community.Purpose: To find out the digital marketing strategies in hospitals in the post-Covid-19 pandemic.Method: This study was conducted descriptively with a literature review approach. The search was carried out on articles published in English and Indonesian from 2014 to 2022 using Google Scholar, with keywords such as